Śmierć, pogrzeb, żałoba - zwyczaje w środowisku polskim na Bukowinie Północnej = Death, funeral and mourning - customs in the Polish environment in northern Bukovina - Pokrzyńska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to the customs that are associated with death, which exist in the praxis and culture of the Polish environment in the northern part of the historical region named Bukovina. The author presents both traditional customs as well as contemporary actions in the event of death of a family or a local community member. She draws attention to the phenomenon of durability and continuity of customs but also to the cultural changes and modern forms which gradually displace former solutions.
Keywords: Śmierć; pogrzeb; żałoba; Polacy na Bukowinie Północnej; death; funeral; mourning; Polish people in the northern Bukovina